Family business and technological innovation : empirical insights from the Italian pharmaceutical industry - Perri, Alessandra; Peruffo, Enzo (Palgrave pivot., 2017)
This book explores technological innovation in family firms, seeking to reconstruct the links between the heterogeneous dimensions of family businesses and their innovative behaviour. Building on and examining the traditional view of family firms as conservative, this book contributes to knowledge surrounding the puzzling role of family firms in technological innovation, with particular focus on the Italian pharmaceutical industry. The authors explore technological advances within the industry in connection with various features of family governance. This thought-provoking study is divided into two parts, the first part providing an overview of current literature on the topic, and the second part analysing the findings of empirical investigation in a specific industry setting. Practitioners and academics of business strategy will find this book extremely useful as it combines both solid theoretical reasoning and robust empirical analysis.